Toxicity research of smouldering and flaming pine timber treated with fire retardant solutions - Karpovič, Zbignev; Šukys, Ritoldas; Gudelis, Rimvydas (Journal of Civil Engineering and Management, 2012)
The emission of toxic gaseous combustion products from timber constructions influences on the time required for evacuation of people from a building during a fire. In order to prolong the time interval until inflammation of timber constructions, fire retardant solutions are used. It is relevant and very important to determine how the emission of toxic gaseous combustion products from pine timber non-treated and treated with fire retardant solutions used in Lithuania differs during thermal destruction. Measuring carbon monoxide (CO) emissions, the paper focuses on toxicity analysis determined by nonstandard and standard research methods of smouldering and flaming pine timber, both non-treated and treated with fire retardant solutions. The description comprises specimens used in research and their preparation, nonstandard and standard research equipment and methods determining toxicity of smouldering and flaming pine timber, both non-treated and treated with fire retardant solutions. The article presents the analysis of experimental results processed by statistical methods.